STUDI EKSISTENSI DAN CITRA MEREK TOKO ROTI BAWEAN “SWEETHEART” BAKERY AND RESTO - Mostar, Jovito Benhart Ramadhan; Rifainy, Amnila Hanisah; Khoirurojak, Mochamad Roihan; Yudawisastra, Helin G (ASH-SHIDQU: JURNAL EKONOMI SYARIAH, 2025)
Bread is a fairly popular carbohydrate substitute for rice. Bakeries have been introduced to Indonesia since the 1930s. One of the shops that has survived until now is the Bawean “Sweetheart” Bakery and Resto shop which started its business in 1946. This study aims to examine the implementation of the existence and brand image of the Bawean “Sweetheart” Bakery and Resto. The brand image of this bakery itself is still traditional where the bread recipes used are still in Dutch which are translated into Indonesian. This research method is exploratory with a prospective case study. Data collection techniques are primary data in the form of interviews and secondary data in the form of observations. The results of the study are expected to be recommendations for the community and academics who want to open a business by making the existence of the Bawean “Sweetheart” Bakery and Resto shop a business reference.